KINERJA KEUANGAN SEBELUM DAN SESUDAH PENERAPAN CORPORATE SOCIAL RESPONSIBILITY (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia 2017-2019) - Lisa Yuliana; Maslichah Maslichah; M. Cholid Mawardi (Universitas Islam Malang, 2021)
This study aims to analyze financial performance before and after the implementation of corporate social responsibility. The population of this study is all manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2017-2019. Number of samples are 14 companies. The data analysis technique used in this study uses formulas to determine the research variables. By calculating the Profitability Ratio (Return On Assets and Return On Equity), Liquidity Ratio (Current Ratio), Solvency Ratio (Debt Ratio), Activity Ratio (Total Asset Turnover) and Market Value Ratio (Earning Per Share). Hypothesis testing to compare financial ratios with non-parametric test tools uses the Wilcoxon Signed Ranks Test and the Kruskal Wallis test. The results of this study indicate that the Wilcoxon Signed Ranks Test and the Kruskal Wallis test on profitability ratios, liquidity ratios, solvency ratios, activity ratios, and market value ratios with an Asymp Sign (2-tailed) value of 0.000 where the value is less than 5%. which means H0 is rejected or there is a significant difference before and after the implementation of CSR in manufacturing companies.Keywords: Profitability, Liquidity, Solvency, Activity, Market Value, Corporate Social Responsibility.